The control of imports and foreign capital in Japan - Ozaki, Robert S. (New York, Praeger, 1972)
This is study of the control of imports and foreign investments in postwar Japan. The subject constitutes a striking feature of foreign economic policy as well as an inseparable component of the overall growth strategy in postwar Japan.
Bibliography: p. [281]-309.
osa; 13/07/18
Loans
Keywords: Import quotas; Foreign trade regulation; Investments, Foreign; Japan